POTENSI EKSTRAK DAUN PANDAN WANGI (Pandanus amaryllifolius Roxb) DALAM MENGHAMBAT PERTUMBUHAN Streptococcus pyogenes - Nurdini, Lia; Dermawan, Asep; Ilmi Sufa, Hafizah; Rohayati (Politeknik Kesehatan Kemenkes Bandung, 2024)
S. pyogenes is the primary cause of acute pharyngitis. The inappropriate, repeated, and irregular use of antibiotics can lead to resistance. One alternative is to utilize plants containing antibacterial compounds. This study aims to identify the concentration and contact time of fragrant pandan leaf extract that has the potential to inhibit the growth of S. pyogenes. The method applied in this study is the disk diffusion test with fragrant pandan leaf extract at concentrations of 20%, 40%, and 60%, with contact periods of 24 hours and 48 hours. Bacitracin was used as a positive control, and 10% DMSO as a negative control. The data were analyzed using a Two Way ANOVA test, showing a significant difference between the extract concentration and contact time on the inhibition zone diameter (p<0.05). The study resulted in an average inhibition zone diameter at a 20% concentration of 9 mm after 24 hours, 40% at 9.9 mm, and 60% at 11 mm. For the 48-hour contact time, the average inhibition zone diameter at a 20% concentration was 8.9 mm, 40% was 9.7 mm, and 60% was 10.8 mm. The average inhibition zone diameter in the positive control (bacitracin) was 18.3 mm, while the negative control showed no inhibition zone.